Curvature coordinates to describe the explosion of Chernobyl’s reactor core in April 1986, using the tensor equations - Matsuki, Y.; Bidyuk, P.I. (Системні дослідження та інформаційні технології, 2017)
This research analyzes the process of the explosion of the reactor core of Chernobyl nuclear plant in April 1986, using the tensor equations. These tensor equations show a movement of a vector in the three dimensional curvature coordinates of time, water flow, and void. The equations shows that this vector moves along the geodesic in the curvature coordinates, which is described by fundamental tensor (gµν), Christoffel symbol (Γαµνσ) and Ricci tensor (Rµν), where µ, ν, σ, α are suffixes that indicate the coordinates. The solution of the tensor equations shows that the geodesic of the vector has a singular point, which describes a turning point of the reactor core from the normal operation to the explosion, which we reported in our previous articles [1, 2]. Проаналізовано процес вибуху активної зони ядерного реактора на Чорнобильській атомній електростанції у квітні 1986 р. за допомогою тензорних рівнянь, які демонструють рух вектора в тривимірних координатах кривої часу, потоку води та пустоти. Рівняння показують, що цей вектор рухається вздовж геодезичної прямої у координатах кривої, яка описується фундаментальним тензором (gµν), символом Крістофеля (Γαµνσ) і тензором Річчі (Rµν), де µ, ν, σ, α — індекси, які позначають координати. Розв’язання тензорних рівнянь показує, що геодезична пряма вектора має сингулярну точку, яка описує точку обертання активної зони ядерного реактора від нормального функціонування до вибуху. Проанализирован процесс взрыва активной зоны ядерного реактора на Чернобыльской атомной электростанции в апреле 1986 г. при помощи тензорных уравнений, которые демонстрируют движение вектора в трехмерных координатах кривой времени, потока воды и пустоты. Уравнения показывают, что этот вектор движется вдоль геодезической прямой в координатах кривой, которая описывается фундаментальным тензором (gµν), символом Кристоффеля (Γαµνσ) и тензором Риччи (Rµν), где µ, ν, σ, α — индексы, обозначающие координаты. Решение тензорных уравнений показывает, что геодезическая прямая вектора имеет сингулярную точку, которая описывает точку вращения активной зоны ядерного реактора от нормального функционирования до взрыва.